THE APPLICATION OF SOCIAL MODEL FOR HANDLING COMMUNICATION OF CHILDREN WITH AUTISM - Kusumastuti, Frida (Master of Communication Science Program, Universitas Diponegoro, 2022)
Borrowing studies on disability discourse, there are two leading models of disability discourse, namely the medical model and the social model (LoBianco & Sheppard-Jones, 2008). Through these two models, the interaction of people with autistic children shows a different way. This study wants to show how the application of social models in handling the communication of children with autism. The case was taken in the life of Ry (14) - an autistic boy living in Malang, East Java. Research was carried out through participant observation, and interviews with the subject, namely Ry's parents. Data findings were analyzed using the concept of disability discourse. The result shows that the Ry family apply the social model more by following a typical child communication pattern but collaborated with social rules that allow both parties to feel comfortable communication. Ry's parents condition the other party that Ry has the potential to interact with-communication by giving detailed information about Ry's uniqueness.